Enhancing immune protection against MERS-CoV: the synergistic effect of proteolytic cleavage sites and the fusion peptide and RBD domain targeting VLP immunization - Oh, Jeein; Park, Uni; Kim, Juhyung; Jeon, Kyeongseok; Kim, Chulwoo; Cho, Nam-Hyuk; Choi, Youn Soo (Frontiers in Immunology, 2023)
The Middle East Respiratory Syndrome Coronavirus (MERS-CoV) is a zoonotic infectious virus that has caused significant outbreaks in the Middle East and beyond. Due to a highly mortality rate, easy transmission, and rapid spread of the MERS-CoV, it remains as a significant public health treat. There is currently no licensed vaccine available to protect against MERS-CoV. In this study, we investigated whether the proteolytic cleavage sites and fusion peptide (PSFP) domain of the MERS-CoV spike (S) protein could be a vaccine target to elicit the MERS-CoV S protein-specific antibody responses and confer immune protection against MERS-CoV infection. Our results demonstrate that immunization of the PSFP domain using virus-like particle (VLP) induced the MERS-CoV S protein-specific IgG antibodies with capacity to neutralize pseudotyped MERS-CoV infection in vitro. Moreover, PSFP VLP immunization showed a synergistic effect on the immune protection against MERS-CoV infection elicited by immunization with VLP expressing the receptor binding domain (RBD) of the S protein. Additionally, immune evasion of MERS-CoV RBD variants from anti-RBD sera was significantly controlled by anti-PSFP sera. Our study demonstrates the potential of VLP immunization targeting the PSFP and RBD domains of the MERS-CoV S protein for the development of effective treatments and vaccines against MERS-CoV and related variants.